2022
DOI: 10.1186/s40461-022-00135-5
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuities in vocational education and training: the influence of early-risk factors and personality constructs on premature training termination and subsequent trajectories

Abstract: Background For adolescents, preventing a premature training termination (PTT) and withdrawal from education and training after a PTT is an important societal task. While studies reveal that early-risk factors such as a low educational background or selected personality constructs are relevant for predicting PTT, less is known about subsequent trajectories after a PTT and the factors that determine them. Methods Using data from the German National E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…Especially immigrants of Turkish origin or from other guest worker countries 10.3389/feduc.2022.894249 had difficulties to complete academic tracks with a general university entrance qualification. Disadvantages regarding track completion were, however, particularly pronounced among students who entered VET after Grade 9 or 10: 37% of immigrants enrolled in VET after Grade 9 or 10 dropped out and did not achieve a vocational qualification, while the dropout rate of natives (26%) was 11 percentage points lower (p < 0.001) (see also Michaelis and Richter, 2022). In contrast, immigrants and natives who switched to upper-secondary vocational schools after Grade 9 or 10 had the same probability to successfully complete these tracks with an upper-secondary degree (mainly with an entrance qualification for university of applied sciences) or to still be enrolled at the last interview available in NEPS.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Especially immigrants of Turkish origin or from other guest worker countries 10.3389/feduc.2022.894249 had difficulties to complete academic tracks with a general university entrance qualification. Disadvantages regarding track completion were, however, particularly pronounced among students who entered VET after Grade 9 or 10: 37% of immigrants enrolled in VET after Grade 9 or 10 dropped out and did not achieve a vocational qualification, while the dropout rate of natives (26%) was 11 percentage points lower (p < 0.001) (see also Michaelis and Richter, 2022). In contrast, immigrants and natives who switched to upper-secondary vocational schools after Grade 9 or 10 had the same probability to successfully complete these tracks with an upper-secondary degree (mainly with an entrance qualification for university of applied sciences) or to still be enrolled at the last interview available in NEPS.…”
Section: Discussionmentioning
confidence: 96%
“…respect, recent findings begin to provide valuable insights into the consequences of immigrant optimism. Recent studies found higher dropout rates at academic tracks (e.g., Birkelund, 2020;Dollmann and Weißmann, 2020), at VET (e.g., Rohrbach-Schmidt and Uhly, 2015;Seidel, 2019;Michaelis and Richter, 2022), but also at higher education (e.g., Müller, 2018;Lörz, 2019;Klein and Neugebauer, 2021) among immigrants.…”
Section: Discussionmentioning
confidence: 99%
“…respect, recent findings begin to provide valuable insights into the consequences of immigrant optimism. Recent studies found higher dropout rates at academic tracks (e.g., Birkelund, 2020;Dollmann and Weißmann, 2020), at VET (e.g., Rohrbach-Schmidt and Uhly, 2015;Seidel, 2019;Michaelis and Richter, 2022), but also at higher education (e.g., Müller, 2018;Lörz, 2019;Klein and Neugebauer, 2021) among immigrants.…”
Section: Discussionmentioning
confidence: 99%
“…Holtmann and Solga (2023) noted a significant correlation between age at the start of the initial VET and dropout, while sex and migration background did not exhibit significant correlations. Conversely, Michaelis and Richter (2022) found that migration background significantly influenced dropout, with no significant impact from gender. In our study, we surveyed sex (0,female; 1,male), age, and migration background using the spoken language at home as an indicator.…”
Section: Control Variablesmentioning
confidence: 90%